Influence of reinforcements on slenderness effects in slender rectangular RC beams - Girija, K.; Menon, Devdas (Journal of Structural Engineering, 2024)
Present code specifications on slender reinforced concrete rectangular (RC) beams impose limits on the slenderness ratio in terms of the beam dimensions. This does not account for the contribution of reinforcements in the beam. This paper reports the results of experiments conducted on slender rectangular RC beams to study the effect of longitudinal and transverse reinforcement ratios on flexural strength. The test results, supported by theoretical formulations, establish that variations in these reinforcement ratios can significantly affect the critical moment capacity, and, in the case of moderately slender beams, can cause reduction in the flexural capacity estimated by conventional methods that ignore slenderness effects.